Medieval surroundings of the Bilyar: concerning the method of research in the settlement pattern and resources potentiality - Shakirov Zufar G. (Поволжская археология, 2014)
The article analyzes the principal concepts and methodological developments, which make it possible to define the territorial and chronological study boundaries of the medieval Bilyar city neighborhood. Based upon a complex mapping of monuments, a territorial framework of the study has been defined, which allows reflecting the dynamics of the historical processes in the 10th through to 15th centuries at all historical stages of the existence of Bilyar related to the functioning of state entities as Volga Bulgaria, the Bulgar Vilayet of the Juchi Ulus, and the Kazan Khanate. For the territory defined, the author's method of research in the spatial features of settlement pattern and resource potential evaluation of Bilyar environs has been provided. This approach consists in taking into account the various natural and social factors that had influenced the economic and demographic indicators of the area.